PREDICTING THE GROWTH CURVE OF BODY WEIGHT IN MALEO BIRDS (MACROCEPHALON MALEO) - Widya Pintaka Bayu Putra (OISAA, 2021)
Maleo bird (Macrocephalon maleo) is the one of protected bird’s species and originated from Sulawesi island of Indonesia. This study was carried out to obtain the growth curve of body weight (BW) in mixed-sex Maleo birds from hatching to yearling ages. The growth curve in this study was calculated with non-linear regression of Logistic (L) and Gompertz (G) models using CurveExprt 1.4. computer program. The primary data in this study was cited from previous study through a literature study. Research showed that the asymptotic weight (A) in birds was 1825.34 g (L) and 3429.23 g (G). The weight of inflection (Wi) in studied birds were 912.67 g (L) and 1260.75 g (G). The time of inflection (ti) in birds was 8.51 months (L) and 11.00 months (G). The maximum growth rate in birds was 159.72 g/month (L) and 151.29 g/month (G). The coefficient of determination (R2) in both models included of very high category (0.80<R2<1.00) but the lower of standard error (SE) value showed in L model. It can be concluded that the non-linear regression of Logistic model can be used as BW predictors in mixed-sex Maleo birds.